2021
DOI: 10.1159/000518178
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conservative and Surgical Treatments in Symptomatic Pregnancy Hydronephrosis

Abstract: <b><i>Objectives:</i></b> This study aimed to evaluate the factors affecting the treatment choice in pregnant women with symptomatic hydronephrosis. <b><i>Methods:</i></b> Hospital records of pregnant women who visited our clinic due to symptomatic hydronephrosis between December 2010 and December 2020 were analysed retrospectively. Patients were divided into 2 groups: conservative and surgical (JJ stent) treatment groups. Age, gestational week, primipara, trimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…They concluded that early surgical intervention is better in patients who do not respond well to conservative management. Intervention is needed if the renal pelvis AP diameter is greater than 16.5 mm in the first and second trimesters but can be up to 27.5 mm till intervention is needed in the third trimester [34].…”
Section: Conservative Management Versus Interventionmentioning
confidence: 99%
“…They concluded that early surgical intervention is better in patients who do not respond well to conservative management. Intervention is needed if the renal pelvis AP diameter is greater than 16.5 mm in the first and second trimesters but can be up to 27.5 mm till intervention is needed in the third trimester [34].…”
Section: Conservative Management Versus Interventionmentioning
confidence: 99%